Fifteen-minute consultation: Practical use of continuous glucose monitoring. Issue 3 (7th May 2021) - Soni, Astha; Wright, Neil; Agwu, Juliana Chizo; Drew, Josephine; Kershaw, Melanie; Moudiotis, Christopher; Regan, Fiona; Williams, Eleri; Timmis, Alison; Ng, Sze May
Abstract : Type 1 diabetes is a self-managed condition. Regular monitoring of blood glucose (BG) levels has been the cornerstone of diabetes management. Finger prick BG testing traditionally has been the standard method employed. More recently, rapid advancements in the development of continuous glucose monitoring devices have led to increased use of technology to help children and young people with diabetes manage their condition. These devices have the potential to improve diabetes control and reduce hypoglycaemia especially if used in conjunction with a pump to automate insulin delivery. This paper aims to provide an update on main CGM devices available and practical considerations for doctors if they come across a child with diabetes who is using one of these devices.